Length–weight relations of fishes (Actinopterygii) from karst streams in the bodoquena plateau, western Brazil - Severo-Neto, Francisco [UNESP]; Lopes, Douglas Alves; Ferreira, Anderson; Martínez, Bruno Téllez; Roque, Fabio de Oliveira (Pensoft Publishers, 2018)
The presently reported study provides the length–weight relations (LWR) for 23 species from headwater streams of the Bodoquena Plateau, which is located on the southern border of the Brazilian Pantanal. The following species were studied Steindachnerina brevipinna (Eigenmann et Eigenmann, 1889); Characidium zebra Eigenmann, 1909; Bryconops melanurus (Bloch, 1794); Aphyocharax dentatus Eigenmann et Kennedy, 1903; Astyanax lacustris Lütken, 1875; Astyanax lineatus (Perugia, 1891); Brachychalcinus retrospina Boulenger, 1892; Creagrutus meridionalis Vari et Harold, 2001; Hemigrammus lunatus Durbin, 1918; Hyphessobrycon eques (Steindachner, 1882); Hyphessobrycon luetkeni (Boulenger, 1887); Jupiaba acanthogaster (Eigenmann, 1911); Moenkhausia bonita Benine, Castro et Sabino, 2004; Odontostilbe pequira (Steindachner, 1882); Piabarchus analis (Eigenmann, 1914); Serrapinus calliurus (Boulenger, 1900); Hoplerythrinus unitaeniatus (Spix et Agassiz, 1829); Hypostomus basilisko Tencatt, Zawadzki et Froelich, 2014; Otocinclus vittatus Regan, 1904; Rineloricaria parva (Boulenger, 1895); Cichlasoma dimerus (Heckel, 1840); Crenicichla lepidota Heckel, 1840; Poecilia reticulata Peters, 1859. Specimens were collected in February and October of 2016. This study represents the first LWR data for 13 species and the maximum standard length for Astyanax lacustris and Moenkhausia bonita.
Keywords: Fish assemblage; Headwaters; Length; LWR; Neotropical; Pantanal; Weight relation